As dinâmicas econômicas, sociais e ambientais na cidade turística de Caldas Novas-GO - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
When observing the social and economic dynamics found in the urban scenario, in particular, in the tourist city of Caldas Novas-GO, we observe several questions and contradictions regarding the use of space and the right to the city, elements that aim for a more urban environment. harmonious in terms of services and structure that are considered basic. These concepts go beyond just scientific elements, but have critical opportunities and even the potential to stir society in the search for a city that provides quality spaces for everyone. In this way, the research demonstrates that, despite several normative means of creating a harmonious urban, in Caldas Novas, it is not exactly what we found. Despite being a tourist destination already consolidated and recognized as hot water tourism, the municipality lives with great contradictions with regard to urban expansion, the use of space and the exploitation of the environment, in addition to the identification of distinct urban spaces one to another. the tourist service, consisting of attractions and structures that characterize the tourist space, and the other depending on the resident community, which in some places does not even have the basics of urban infrastructure. This is necessary for the municipality, which counts on the environment for the continuity of activities related to tourism, and, finally, to observe the relations of the public power in the provision of services in urban spaces, in the peripheral neighborhoods where most of the population resides. of the city's working class.
Keywords: Espaço urbano; Expansão urbana; Direito à cidade; Cidade turística; Touristic city; Urban space; CIENCIAS SOCIAIS APLICADAS::TURISMO; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL; SOCIOLOGIA::SOCIOLOGIA URBANA